Great expectations and interwar realities : Hungarian cultural diplomacy, 1918-1941 - Nagy, Zsolt, 1973- (Central European University Press, 2017)
"Great Expectations and Postwar Realities is an examination of the practice variously referred to as 'cultural diplomacy, ' 'self-advertisement, ' 'image cultivation, ' 'image projection, ' 'public relations, ' 'soft power, ' 'nation-branding, ' 'perception management, ' 'national reputation management, ' and, most recently, 'public diplomacy.' By investigating the intersection of diplomacy, national identity construction, and cultural production, my study evaluates the promises and limitations of interwar Hungarian cultural diplomacy. It asks two questions: What was the value of such practices when employed by a state that lacked material and non-material power? In which ways did the country's cultural-diplomatic endeavors contribute to its postwar nation-building project? In posing these questions, Great Expectations and Postwar Realities, while rooted in Hungary, examines larger themes such as the nature of interwar international relations and the complexities of national identity construction. Hungarian cultural diplomacy had a great impact, if for different reasons than historians have often thought. For while cultural diplomacy helps us to understand the ways in which small states exploited the gaps in the international system, its most enduring achievements are connected with domestic development"--Introduction.